2007
DOI: 10.1016/j.bbi.2007.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Infection-induced viscerosensory signals from the gut enhance anxiety: Implications for psychoneuroimmunology

Abstract: Infection and inflammation lead to changes in mood and cognition. Although the "classic" sickness behavior syndrome, involving fatigue, social withdrawal, and loss of appetites are most familiar, other emotional responses accompany immune activation, including anxiety. Recent studies have shown that gastrointestinal bacterial infections lead to enhanced anxiety-like behavior in mice. The bacteria-induced signal is most likely carried by vagal sensory neurons, and occurs early on (within six hours) during the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 32 publications
(40 reference statements)
8
78
0
3
Order By: Relevance
“…By directly recognizing a characteristic microbial component and not only a generic inflammatory event, DRGs sensory neurons could be the first element in a labeled neural pathway, conveying to the CNS early and specific information on the nature and localization of microorganisms detected in the intestinal wall. Involvement of sensory pathways in conveying non-circulating microorganism-related signals has already been shown for the vagus nerve (Goehler et al 2005,2007), and because its sensory ganglion expresses TLR4 (Hosoi et al 2005), a direct activation by pathogens has been hypothesized (Goehler et al 2007). It has also been shown that electrophysiological responses of DRGs sensory neurons projecting to the intestine can be modulated by oral inoculation of probiotics (Kamiya et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…By directly recognizing a characteristic microbial component and not only a generic inflammatory event, DRGs sensory neurons could be the first element in a labeled neural pathway, conveying to the CNS early and specific information on the nature and localization of microorganisms detected in the intestinal wall. Involvement of sensory pathways in conveying non-circulating microorganism-related signals has already been shown for the vagus nerve (Goehler et al 2005,2007), and because its sensory ganglion expresses TLR4 (Hosoi et al 2005), a direct activation by pathogens has been hypothesized (Goehler et al 2007). It has also been shown that electrophysiological responses of DRGs sensory neurons projecting to the intestine can be modulated by oral inoculation of probiotics (Kamiya et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, production of the SCFA butyrate by bacteria affects gene expression and the phenotype of enteric neurons in a similar manner to that observed in the colons of patients treated with prokinetic agents (166,169). Gastrointestinal microbiota may also contribute to the affective symptoms associated with GI disorders by impacting the CNS via immune, hormonal, and neural mechanisms (17,69,155). Preliminary studies have demonstrated that alterations in the GI microbiota can lead to long-term increased anxiety (69,115,116) and altered exploratory behavior in mice (18,19).…”
Section: The Intestinal Microbiota and Brain-gut Axismentioning
confidence: 99%
“…Gastrointestinal microbiota may also contribute to the affective symptoms associated with GI disorders by impacting the CNS via immune, hormonal, and neural mechanisms (17,69,155). Preliminary studies have demonstrated that alterations in the GI microbiota can lead to long-term increased anxiety (69,115,116) and altered exploratory behavior in mice (18,19). Similarly, psychosocial stressors can change the composition of the intestinal microbiota and affect the brain-gut axis function (6,7,119).…”
Section: The Intestinal Microbiota and Brain-gut Axismentioning
confidence: 99%
“…18 reFerences "Our paper supports a second therapeutic strategy for treating IBD-highly selective nicotinic receptor agonists. "…”
Section: Model Behaviormentioning
confidence: 99%